Hydrated Peridotite–Basaltic Melt Interaction Part II: Fast Assimilation of Serpentinized Mantle by Basaltic Magma - Borisova, Anastassia Y.; Zagrtdenov, Nail R.; Toplis, Michael J.; Ceuleneer, Georges; Safonov, Oleg G.; Pokrovski, Gleb S.; Jochum, Klaus Peter; Stoll, Brigitte; Weis, Ulrike; Shcheka, Svyatoslav; Bychkov, Andrey Y. (Frontiers in Earth Science, 2020)
The most abundant terrestrial lavas, mid-ocean ridge and ocean island basalt (MORB and OIB), are commonly considered to be derived from a depleted MORB-mantle component (DMM) and more specific, variably enriched mantle plume sources. However, findings of oceanic lavas and mafic cumulates issued from melts, enriched in chlorine and having a radiogenic 87Sr/86Sr ratio, can be attributed to an interaction between the asthenosphere-derived melts and lithospheric peridotite variably hydrated due to penetration of hydrothermal water down to and below Moho level. To constrain mechanisms and rates responsible for the interaction, we report results of 15 experiments of reaction between serpentinite and tholeiitic basaltic melt at 0.2 - 1.0 GPa and 1250 - 1300°C. Results show that the reaction proceeds via a multi-stage mechanism: (i) transformation of serpentinite into Cr-rich spinel-bearing harzburgite (Fo92-95 mol.%) containing pore fluid, (ii) partial melting and dissolution of the harzburgite assemblage with formation of interstitial hydrous melts (up to 57 – 60 wt% of SiO2 contents at 0.5 GPa pressure), and (iii) final assimilation of the Cr-rich spinel-bearing harzburgite/dunite and formation of hybrid basaltic melts with 12 – 13 wt.% of MgO and elevated Cr (up to ~500 ppm) and Ni (up to ~200 ppm) contents. Assimilation of serpentinite by basaltic melt may occur under elevated melt/rock ratios (>2) and may lead to chromitite formation. We show that hybrid magmas produced by the progressive assimilation of serpentinized lithospheric mantle may be recognized by high Mg-numbers and high Cr and Ni contents of olivine and pyroxenes, an excess of SiO2, H2O and halogens in the melts, and some unusual isotopic composition (e.g., radiogenic 87Sr/86Sr, non-mantle δ18O). Our experiments provide evidence that MORB and high-Mg-Cr orthopyroxene-rich cumulates depleted in incompatible elements can be produced from common mid-ocean ridge basaltic melts modified by reaction with hydrated lithospheric peridotite. We established that the rate of assimilation of serpentinized peridotite is controlled by silica diffusion in the reacting hydrous basaltic melt. Our study challenges traditional interpretation of the variations in MORB and OIB chemical and isotopic composition in terms of deep mantle plume source heterogeneities or/and degrees of partial melting.